INDEPENDENSI, KOMPETENSI, PENGALAMAN KERJA, DAN DUE PROFESSIONAL CARE: PENGARUHNYA TERHADAP KUALITAS AUDIT YANG DIMODERASI DENGAN ETIKA PROFESI (Studi Empiris pada Kantor Akuntan Publik se-Jawa Tengah dan DIY) - Ningtyas, Widia Arum; Aris, Mochammad Abdul (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study was to analyze the effect of the independence, competence, work experience ,andÂ  due professional care to the quality of the audit and the independence, competence, work experience and due professional care on audit quality that is moderated by the ethics of the profession, especially at the internal auditors working in public accounting in Cental Java and Yogyakarta. The population in this study are all auditors who work in public accounting in Central Java and Yogyakarta. The sampling technique used was purposive sampling method, with the acquisition of a sample of 78 respondents. The primary data collection using the questionnaire. The data are analyzed using multiple linear regression analysis and moderated regression analysis (MRA). The results of the analysis proved that the variable independence, competence, work experience, due professional care, the interaction of the independence of the ethics of the profession, and the interaction of experience working with professional ethics partially significant effect on audit quality, while the interaction of competence with professional ethics and interaction due professional care with ethics profession partially no significant effect on audit quality.